Watershed services payments to smallholders in the Brazilian Amazon: challenges and perspectives - Ricardo de Oliveira Figueiredo (Revista Ambiente & Água, 2013)
Several hydrobiogeochemical research activities have been conducted in the Eastern Amazon, contributing to the understanding of how changes in forests and agro-ecosystems affect the provision of services to ecosystems. The findings have demonstrated that good agricultural practices and the presence of natural secondary vegetation favored by the management of small family farms are important factors for hydrobiogeochemical cycling, aquatic ecosystem conservation, soil conservation, and mitigation of trace gases emissions from biomass burning in Amazonian small catchments. Two challenges for watershed service management arise in this context. First, low population densities and the relatively flat landscape mean that a critical mass of downstream beneficiaries of such services - a prerequisite for public intervention is more difficult to identify than in more densely populated mountainous areas. Second, although watershed service providers (farmers) are also to a considerable extent service beneficiaries, conflicts over land and cultural heterogeneities among settlers inhibit local collective action to safeguard the quality of stream water. Including small landholders in carbon payment schemes that compensate for the maintenance of riverbank vegetation would appear to be a cost-effective means to secure watershed services as additional benefits of forest-based mitigation of climate change.